2009
DOI: 10.1073/pnas.0909097107
|View full text |Cite
|
Sign up to set email alerts
|

Cleistogamous flowering in barley arises from the suppression of microRNA-guided HvAP2 mRNA cleavage

Abstract: The cleistogamous flower sheds its pollen before opening, forcing plants with this habit to be almost entirely autogamous. Cleistogamy also provides a means of escape from cereal head blight infection and minimizes pollen-mediated gene flow. The lodicule in cleistogamous barley is atrophied. We have isolated cleistogamy 1 (Cly1) by positional cloning and show that it encodes a transcription factor containing two AP2 domains and a putative microRNA miR172 targeting site, which is an ortholog of Arabidopsis thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
192
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 198 publications
(200 citation statements)
references
References 40 publications
7
192
1
Order By: Relevance
“…Cloning of the Lax-a gene might open future perspectives in plant breeding, provided that adverse phenotypic effects can be moderated or eliminated. Lax florets can open without the impetus force of lodicules, which were reported previously to be essential for open flowering in barley (Nair et al, 2010). Since the wild-type structures of the lemma and palea help keep barley flowers closed during anthesis, the open-flowering lax-a phenotype may help to achieve open flowering independent of lodicules to facilitate hybrid breeding in barley.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloning of the Lax-a gene might open future perspectives in plant breeding, provided that adverse phenotypic effects can be moderated or eliminated. Lax florets can open without the impetus force of lodicules, which were reported previously to be essential for open flowering in barley (Nair et al, 2010). Since the wild-type structures of the lemma and palea help keep barley flowers closed during anthesis, the open-flowering lax-a phenotype may help to achieve open flowering independent of lodicules to facilitate hybrid breeding in barley.…”
Section: Resultsmentioning
confidence: 99%
“…The genes controlling barley inflorescence architecture and development have only been revealed for a few characters. Major genes that control row type (vrs1 [Komatsuda et al, 2007], intermedium-c [Ramsay et al, 2011], and vrs4 [Koppolu et al, 2013]), the conversion of awns into an extra floret (Hooded; Müller et al, 1995), adherence of the hull to the caryopsis (nud; Taketa et al, 2008), swelling of lodicules conferring open/ closed flowering (cleistogamy/chasmogamy) and spike density (cly1 [Nair et al, 2010] and zeo1 [Houston et al, 2013]), elongation of awns and pistil morphology (lks2; Yuo et al, 2012), suppression of bracts (trd1; Whipple et al, 2010;Houston et al, 2012), spike branching (com2; Poursarebani et al, 2015), and brittleness of the rachis (btr1/btr2; Pourkheirandish et al, 2015) were recently cloned. A large number of additional morphological mutants that influence barley inflorescence development (Forster et al, 2007) also have been described, and the underlying genes need to be identified to reach a more complete understanding of the regulatory pathways controlling barley spike architecture and development (Forster et al, 2007).…”
mentioning
confidence: 99%
“…The cleistogamous state in barley is recessive and is under the control of a single gene at the cleistogamy 1 (cly1) locus, which maps to the long arm of chromosome 2H. Nair et al [28] have isolated cly1 by positional cloning. This gene is a transcription factor containing two AP2 domains and a putative miR172 targeting site, and codes for an AP2-protein that inhibits the development of the lodicule, avoiding the opening of the flower and the subsequent pollen dispersal and cross-pollination.…”
Section: Cleistogamymentioning
confidence: 99%
“…The size of a sliding window was chosen to include 30 adjacent positions in the genetic map. Yan et al, 2006;Komatsuda et al, 2007;Sutton et al, 2007;Taketa et al, 2008;Nair et al, 2010;Ramsay et al, 2011) were searched for the presence of flanking or cosegregating markers and gene sequences with BLASTN (Altschul et al, 1990), or BAC clone identifiers from the original publications were identified in the FPC database of fingerprinted contigs.…”
Section: Distribution Of Bac Librariesmentioning
confidence: 99%